Reciprocal Associations Between Eating Pathology and Parent-Daughter Relationships Across Adolescence: A Monozygotic Twin Differences Study - Korotana, Laurel M.; von Ranson, Kristin M.; Wilson, Sylia; Iacono, William G. (Frontiers in Psychology, 2018)
This prospective study explored longitudinal, bidirectional associations between eating pathology and perceptions of the parent-child relationship (i.e., parent-child regard and involvement) across adolescence. Specifically, this study examined whether twin differences in mother-daughter and father-daughter relationship problems emerged as a risk factor for, or outcome of, twin differences in eating pathology. By examining twin differences, this study explored associations between variables while controlling for shared environmental and genetic effects. A population-based sample of 446 monozygotic twin girls and their mothers completed questionnaires when twins were approximately 11, 14, and 17 years. Responses were analyzed using longitudinal cross-lagged models. Overall, few strong longitudinal associations were observed. Where longitudinal associations emerged, overall patterns indicated reciprocal associations that shifted across adolescence. Whereas twin differences in parent-daughter relationship variables more often predicted later twin differences in eating pathology across early adolescence, conversely, twin differences in eating pathology more often predicted later twin differences in parent-daughter relationship variables across later adolescence. In particular, the twin who reported greater eating pathology later reported more negative perceptions of the father-daughter relationship, as compared to her co-twin. Findings raise questions for future research regarding parental – in particular, paternal – responses to adolescent eating pathology and suggest the potential importance of efforts to support the parent-daughter relationship within the context of adolescent eating pathology.